Does leadership development alter the perspectives of NHS managers?. Issue 2 (2nd February 2019) - Percival, Alex; Best, Stephanie
Abstract : Leadership and leadership development are widely discussed topics in the NHS, and common agreement on the best way forward is rarely agreed upon. Examining the experiences of NHS managers undertaking leadership development offers an insight into the impact training these leaders can have. Five non-clinical managers, who had recently completed a leadership development programme, were interviewed to explore their perceptions of the benefits and challenges associated with leadership development. The study respondents cited personal benefits to their participation in the Leadership Development Programme, and how they were able to bring this learning into their workplace. However, limited evidence that personal benefits are translated into organisational gains was found. Translation barriers were explored, and a key obstacle was the lack of involvement of senior managers in the programme. Areas for future study are identified, including the need for longitudinal research to determine the value of leadership development in an organisation.